The species of Eulaema (Eulaema) Lepeletier, 1841 (Hymenoptera: Apidae: Euglossina) from eastern Brazil, with description of Eulaema quadragintanovem sp. n. from the state of Ceará - Nemésio, André; Ferrari, Rafael R. (Zootaxa, 2012)
Eulaema (Eulaema) quadragintanovem sp. n., a species similar to Eulaema (E.) seabrai Moure, 1960 and Eulaema (E.)helvola Moure, 2003, is described from ‘Serra do Baturité’ and ‘Parque Nacional de Ubajara’, state of Ceará, northeasternBrazil. This species seems to be restricted to ‘brejos de altitude’—Atlantic Forest physiognomies at the top of mountainsin northeastern Brazil—in the state of Ceará. Since these forested areas are rapidly disappearing, it is possible that in thenear future no suitable habitat will be left for this species. The recent record of Eulaema bombiformis (Packard, 1869) inCeará is also discussed. Six species of Eulaema (Eulaema) are now known to occur in eastern Brazil and an updated identification key for them is provided.